The Correlation Between Gravidity and Hypertension in Pregnancy at Baamang 2 Health Center Sampit 2023 - Yayu Yuliarti; Rini Lestari (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2024)
Hypertension in pregnancy is still one of the three biggest contributors to maternal mortality and the percentage of cases is still quite high both in the world, nationally, provincially, and district/city. The most common causes of death in Central Kalimantan in 2022 are bleeding at 50.7% and hypertension in pregnancy at 14.2%. The regency/city with the highest number of maternal deaths in Central Kalimantan is East Kotawaringin Regency with 11 cases in 2022, most of these maternal deaths occur due to bleeding, hypertension in pregnancy, and other causes. Some of the factors that cause HDK include age, nutritional status, history of diabetes mellitus (DM), genetics, history of hypertension, multiple pregnancies, stress/anxiety, and related to gravidity. The purpose of this study is to determine the relationship between gravidity and the incidence of hypertension in pregnancy at the Baamang 2 Sampit Health Center in 2023. This research method uses a quantitative method that is analytical with a cross sectional approach. The research samples were taken using a total sampling technique of 55 pregnant women who experienced hypertension in pregnancy at the Baamang 2 Sampit Health Center in 2023. The analysis method used is the Spearman Rank test. Based on the results of data processing through the Spearman Rank test, a ρ value of 0.491 or greater than 0.05 was obtained. The conclusion from the results of data analysis is that there is no significant correlation between gravidity and the incidence of hypertension in pregnancy at the Baamang 2 Sampit Health Center in 2023.